National education ideology as the orientation of the school culture development policy at SMA N 1 and SMA N 3 Yogyakarta - Lusila Andriani Purwastuti; Shodiq A Kuntoro; Dwi Siswoyo (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2017)
This study aimed at describing the national education ideology as the orientation of the school culture development policy at SMA N 1 and SMAN 3 Yogyakarta. This research employed the qualitative approach through ethnography method. The subjects of the research were the school community. The object was the implementation of Pancasila on the development of the school culture. The data were collected through interviews, observations, and documentation. The data were analyzed using ethnography analysis as suggested by Spradley and they were validated by data triangulation and member checks. The results show that the national education ideology as the orientation of the school culture development is understood: (1) as an open ideology; (2) implemented on the basis value; instrumental values; the value of practices in the school culture; (3) The school culture in SMA N 1 and SMA N 3 is the implementation and contextualization of the values of Pancasila, along with the uniqueness of SMA N 1 with its “Teladan” icon which represents the religious morality and intellectual, as well as at SMA N 3 with its “Padmanaba” icon representing noble behavior. (4)  Both schools have developed the school culture, namely: religious morality, social-culture, intellectual, and environment/management/leadership.